Analisis Yuridis Penggunaan Rekening Pribadi Orang Lain dalam Tindak Pidana Judi Online (Studi Putusan No 138/PID.SUS /2024/PN. BTM): Penelitian - Jasmine Azura Nasution; Gousta Feriza (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This research examines the juridical aspects of utilizing third-party personal bank accounts in online gambling crimes, focusing on the study of Decision Number 138/Pid.Sus/2024/PN Batam. The study is prompted by the increasing prevalence of online gambling practices that exploit third-party accounts to disguise financial transaction flows. The legal problem investigates the application of criminal liability under the Personal Data Protection Law and evaluates the judge's legal considerations through the lens of John Rawls' theory of justice. This study employs a normative juridical method with a case study approach, drawing from primary legal materials such as statutory regulations and court decisions, as well as secondary legal materials including legal doctrines and literature. Data analysis is conducted descriptively by applying Gustav Radbruch's theory of legal certainty to assess the consistency of legal norm application, and John Rawls' theory of justice to evaluate substantive justice for the aggrieved parties. The results indicate that the unauthorized use of bank accounts fulfills the elements of unlawful personal data processing, specifically regarding personal financial data as regulated under the Personal Data Protection Law. However, the court only applied the Electronic Information and Transactions (ITE) Law and the Money Laundering (TPPU) Law without integrating the Personal Data Protection Law, leading to normative inconsistencies and a failure to provide optimal protection for personal data subjects.